In-situ measurement of rake face temperatures in orthogonal cutting. Issue 1 (2020) - Saelzer, J.; Berger, S.; Iovkov, I.; Zabel, A.; Biermann, D.
Abstract: In machining, the thermal load significantly influences the tool wear and the workpiece quality, thus limiting the productivity. Therefore, a new experimental setup for the high-speed measurement of the rake face temperature in orthogonal cutting without substantially affecting the chip formation was developed. The investigations focus on the influence of different rake face preparation methods and cutting parameters on the temperature of the rake face, measured in the immediate vicinity of the cutting edge. The presented results significantly improve the understanding of the process and provide new insights for the tool development and the validation of cutting models.